If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (e + 1) * 5 = 10 Reorder the terms: (1 + e) * 5 = 10 Reorder the terms for easier multiplication: 5(1 + e) = 10 (1 * 5 + e * 5) = 10 (5 + 5e) = 10 Solving 5 + 5e = 10 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 5e = 10 + -5 Combine like terms: 5 + -5 = 0 0 + 5e = 10 + -5 5e = 10 + -5 Combine like terms: 10 + -5 = 5 5e = 5 Divide each side by '5'. e = 1 Simplifying e = 1
| c=15+4*50 | | 2(z+2)-5=7 | | X^2y+3xy+xy^2=0 | | 2x^2-4x^3+12x-6=0 | | 500x-x=300 | | -5x+5=6-4x | | 2+2x=4x-14 | | 3(0--16)= | | -6x+8=20-10x | | 3(1+x)=14-x | | -3(1+x)=14-r | | -1+4x=-3x-85 | | 2x-24=3x+4 | | 1/2(x-8)-6=24 | | 2a-3b=-8 | | 5a+6b=-2 | | 6a+b=-2 | | 3x-8=-2-3x | | -5r-5s=25 | | b+14=56 | | 8x+2(1.5x)=400 | | 4r+s=-14 | | (6x-20)= | | -7x+11=60 | | -2x-4=-x+0 | | (t+3)(t+8)=t(t+5)+168 | | 18-2z=6-4 | | -6y=36x-72 | | 2x^3+4x^2+10x=0 | | 7x-2=34+x | | 4y+7y=66 | | 5n+10-8=2x |